(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the stress situations that arise in students in the modern educational process, their causes, and their negative impact on the psyche of students. The article also describes effective methods and recommendations aimed at increasing the psychological stability of students, managing emotional stress, and preventing a decrease in academic performance.